An Overview on Local and Global Branded Products for Knit Apparels in Bangladesh and their effect on consumer behavior - Hridoy, Toukir Ahmed; Uddin, Md. Mazbah; Rupak, Mashiur; Hossain, Md. Abdullah Al; Dip, Tanvir Mahady; Ahmed, Md. Faisal (International Journal of Scientific Research and Management (IJSRM), 2019)
Abstract:The project mainly deals with detailed study on export oriented & local knit brands & their products, while taking account of various aspects such as – product type, age group, construction of fabric, fabric sourcing, fabric supplier, fabric cost, FOB cost of garments, accessories sourcing & some activities towards sustainability of brands. In this project samples are collected randomly from the merchandising departments of different company & buying houses. Brands are selected in convenient method. We also selected some renowned local brand randomly. Quantitative data & qualitative data are collected through some questionnaires & then they are analyzed. The export oriented brands are selected for the study from North America, South America & Europe region. The result visualizes the picture of detailed study on export oriented & local knit brands & some drawbacks of our local brand has been discovered with some recommendation of appropriate solutions. A detailed survey was also conducted to find out how different aspects of the brands affect consumer behavior.